ETIOLOGICAL RISK FACTORS FOR NEONATAL JAUNDICE. - Irfan Sarwar1, Attiya Ayaz2, Kishwar Ammir3, Nusrat Bashir4, Taj Muhammad5, Azizullah Langah6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: globally around 1.1 million babies born develop the condition of hyperbilirubinemia, with a small number of cases also developing complications that can proceed into fatal outcomes OBJECTIVE: The current study was aimed at investigating the etiological risk factors for neonatal jaundice. DESIGN: Quantitative research design DURATION: Nov 2019 to Feb 2021 in Pediatrics Unit, Ayub Teaching Hospital, Abbottabad METHOD: The study utilized correlation analysis through SPSS to obtain statistical association of the chosen variables with outcomes. RESULT: The research found that among the variables selected, umbilical vein catheterization and respiratory distress are significant risk factors for neonatal jaundice occurrence. CONCLUSION: Findings on this to subject have led to the conclusion that neonatal jaundice complications that affect the brain of the baby are most likely to cause higher death rates, as meningitis and sepsis may enable morbid outcomes. However, further research is required into the subjects, in order to differentiate between manageable complications hypoxic ischemic encephalopathy and conditions in which fatality becomes imminent.